VD_FINDINFO Décision / 2014 / 383 vom 30. April 2014 - VD Tribunal cantonal (2014)
RISQUE DE FUITE, RISQUE DE RÉCIDIVE, RISQUE DE COLLUSION | 138 ch. 1 CP, 139 ch. 1 CP, 186 CP, 19a LStup, 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)